Block Multistep Methods for Solving Ordinary Differential Equations - Ibrahim, Zarina Bibi (2006)
Multistep methods for the solution of systems of Ordinary Differential Equations (ODEs) were described. The first part of the thesis is about the construction and derivation of new Block Backward Differentiation Formula (BBDF) method of constant step size and variable step size for solving first order stiff Initial Value Problems (IVPs). Their regions of stability were presented and numerical results of the methods were compared with existing methods.